2020
DOI: 10.1111/anu.13107
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofmyo‐inositol on growth performance, body composition, antioxidant status, non‐specific immunity and lipid metabolism of juvenile Chinese mitten crab (Eriocheir sinensis)

Abstract: This study evaluated the effects of dietary myo‐inositol (MI) levels on growth, body composition, antioxidant status, non‐specific immunity and lipid metabolism in juvenile Chinese mitten crab (Eriocheir sinensis). A total of 960 crabs was fed with six diets supplemented with graded levels of MI (0, 204, 406, 810, 1,650 and 3,211 mg/kg) for 8 weeks. The crabs fed with diets containing 1,650 mg/kg MI had significantly higher final body weight, weight gain and specific growth rate than those fed 0, 204, 406 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…Moreover, the activities of GST/GOT and ALT/GPT were the most sensitive indicators of liver cell damage, which is increased by dietary MI, this indicates that the addition of MI alleviates the damage of liver cells and avoids the formation of fatty liver [ 77 ]. AKP and ACP are essential enzymes for growth metabolism, homeostasis and health [ 17 , 78 , 79 ]. Therefore, the activities of AKP and ACP in the liver tissue also indirectly reflect the health of the liver [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the activities of GST/GOT and ALT/GPT were the most sensitive indicators of liver cell damage, which is increased by dietary MI, this indicates that the addition of MI alleviates the damage of liver cells and avoids the formation of fatty liver [ 77 ]. AKP and ACP are essential enzymes for growth metabolism, homeostasis and health [ 17 , 78 , 79 ]. Therefore, the activities of AKP and ACP in the liver tissue also indirectly reflect the health of the liver [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Weight gain (WG %) = 100 × (final body weight-initial body weight)/initial body weight; Survival rate (SR %) = 100 × (final fish number/initial fish number); Feed conversion ratio (FCR) = total feed intake weight/(final body weight-initial body weight); Condition factor (CF %) = 100 × wet body weight/body length; Hepatosomatic index (HSI %) = 100 × wet hepatopancreas weight/wet body weight; Visceral index (VIS %) = 100 × wet visceral weight/wet body weight [13,17].…”
Section: Growth Performance and Body Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that there was a close link between the regulation of AMPK activity and IP3R mediated Ca 2+ signalling pathway (27,28) . So far, many investigations have reported that MI plays a crucial part in the regulation of lipid metabolism in aquatic animals (13,15,29) . However, in contrast, no information has been reported on the specific molecular mechanism of MI regulating lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, lipid metabolism mediated by dietary MI was explored at different lipid levels to understand the role of MI in promotion of lipid utilization in crustacean. were prepared with the process in detail described in our previous study (29) . The experimental diets were stored at -20 ℃ until use.…”
Section: Introductionmentioning
confidence: 99%